THE IMPORTANCE OF FREE ECONOMIC ZONES IN THE DEVELOPMENT OF ENTERPRISES IN THE MARKET ECONOMY - Shakirova Gulbahor Sharipdjanovna (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
This article presents ways to develop the country's economy, especially industrial enterprises through the establishment of free economic zones and the use of sustainable development models with the implementation of clearly targeted programs.